(untitled) (Research, Society and Development, 2021)
The restriction use of antimicrobials as growth promoters in the production of broiler chickens has proven to be a major challenge. The use of alternative molecules, which have antimicrobial properties, aims to replace these drugs. Essential oils are molecules with great potential to replace growth promoters. The objective of this trial was to evaluate the use of essential oils derived from Eucalyptus globulus, Cinnamomum zeylanicus and Origanum vulgare via drinking water for broiler chickens. 450 COBB male chicks were used, distributed by experimental design, consisting of four treatments consisting of six replicates, with 15 animals in each replicate. The experiment consisted of negative control, positive control (2ppm flavomycin via feed), cinnamon oil + oregano (300 ml/1000L), and eucalyptus oil (300 ml/1000L). Differences were observed in zootechnical performance (p<0.05), whose broilers supplemented with eucalyptus oil had higher body weight than those fed with flavomycin at 20 days of age. The blood biochemical parameters showed difference only on the levels of uric acid in the diet of animals, whose birds belonging to the group that received flavomycin showed higher levels (P=0.038) when compared to birds submitted to the other treatments. The other parameters evaluated did not change (P>0.05), as well as the intestinal histomorphometric parameters (P>0.05). It concluded that the essential oils were able to replace flavomycin as a growth promoter, ensuring adequate zootechnical performance and without affecting the animals’ health.